Classification of cubic equations - Mačys, Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2018)
Rather unexpectably all real equations of the fourth degree are solvable by real means. So we can classify all real equations of the third and fourth degree. In this article we classify real cubics. The real quartics will be classified in another article.